Research on Time-dependent Reliability of Subway Gearboxes Based on the Response Surface Method - Pei Bang; Li Zhiyuan; Li Xuefei; Chen Zhuo; He Penghui; Huang Xiaodan (Jixie chuandong)
As the core components of metro vehicles, the reliability of metro gearboxes determines the reliability of the whole train. The operation process of subway includes start-up, continuity, high-speed and short circuit conditions. In short circuit conditions, the box body has the maximum stress and the lowest reliability. According to the test requirements of national standard “Railway applications—Rolling stock equipment—Shock and vibration tests”, the reliability analysis of metro gearboxes in abnormal condition (condition 1) and short circuit condition (condition 2) occurring in actual operation is carried out. Thus, the influence of casting tolerance, material parameters and input torque uncertainties on the maximum equivalent stress and maximum deformation of the box body are considered. The CCD experimental design method is used to calculate the sample and fit the response surface, and the static reliability is obtained combined with Monte Carlo sampling. On this basis, combined with the order statistic theory, the reliability of the box with the number of loads is obtained. The results show that the reliability of the box body is still very high and meets the design requirements after 100 thousand loads under the two working conditions. According to the time-dependent reliability diagram, although the mean value of stress in working condition 2 is smaller than that in working condition 1, the variance is larger than that in working condition 1, which leads to the reliability decline rate of working condition 2 is greater than that in working condition 1. Therefore, the dispersion of stress should be reduced to increase the reliability during operation.